Accessing new 2D semiconductors with optical band gap: synthesis of iron-intercalated titanium diselenide thin films via LPCVD. Issue 40 (20th June 2018) - Sanchez-Perez, Clara; Knapp, Caroline E.; Colman, Ross H.; Sotelo-Vazquez, Carlos; Oilunkaniemi, Raija; Laitinen, Risto S.; Carmalt, Claire J.
Abstract : Fe-doped TiSe2 thin-films were synthesized via low pressure chemical vapor deposition (LPCVD) of a single source precursor: [Fe(η 5 -C5 H4 Se)2 Ti(η 5 -C5 H5 )2 ]2 (1 ). Abstract : Fe-doped TiSe2 thin-films were synthesized via low pressure chemical vapor deposition (LPCVD) of a single source precursor: [Fe(η 5 -C5 H4 Se)2 Ti(η 5 -C5 H5 )2 ]2 (1 ). Samples were heated at 1000 °C for 1–18 h and cooled to room temperature following two different protocols, which promoted the formation of different phases. The resulting films were analyzed by grazing incidence X-ray diffraction (GIXRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscope (SEM) and UV/vis spectroscopy. An investigation of the Fe doping limit from a parallel pyrolysis study of Fe x TiSe2 powders produced in situ during LPCVD depositions has shown an increase in the Fe–TiSe2 –Fe layer width with Fe at% increase. Powders were analyzed using powder X-ray diffraction (PXRD) involving Rietveld refinement and XPS. UV/vis measurements of the semiconducting thin films show a shift in band gap with iron doping from 0.1 eV (TiSe2 ) to 1.46 eV (Fe0.46 TiSe2 ).